Gérard Vergnaud in action - Helenius, Ola; Ahl, Linda Marie (NOMAD Nordic Studies in Mathematics Education, 2022)
We have contemplated what we could add to the description of the legacy of Gérard Vergnaud, and have realized that we have at least one expe- rience that is probably not shared by many researchers in mathematics education ...